Recent advances in in-vitro meat production - Kumar, Pavan; Sharma, Neelesh; Narnoliya, Lokesh Kumar; Verma, Akhilesh Kumar; Mehta, Nitin; Bhavsar, Prakrutik Prafulchandra; Kumar, Arvind; Lee, Sun-Jin; Sazili, Awis Qurni (Sciendo, 2024)
In-vitro meat production has entered into the phase of pilot-commercial scale production from the conceptual-laboratory phase. The main challenge for in-vitro meat production on a commercial scale is the very high cost of its production, mainly due to the cost of cell culture media, growth regulators, and the requirement of highly skilled manpower. The development of serum-free and animal-free culture media with plant, microbial, and fungi-derived compounds through recombinant technology and media recycling is crucial for scaling up in-vitro meat production and reducing the price of the end products. The proper design of bioreactors specific to in-vitro meat production, their automation, utilization of natural and edible scaffolds, and microcarriers made up of edible materials are the present focus of researchers. The co-culturing by proliferating various cells such as adipocytes, chondrocytes, fibroblasts, and endothelial cells are applied for imparting textural and organoleptic attributes to developed products similar to conventional meat. The industrial process to produce in-vitro meat needs a clear synergy between the biological, chemical, technical, and industrial fields because at the moment the main research focus is on the development and improvement of cell lines available to set up cell culture and culture media, bioreactors, cell lines, scaffolding, and biofabrication. The research on in vitro meat is limited by the fact that from the industry the protocols are not properly divulgated.